2019
DOI: 10.1111/jfpp.14108
|View full text |Cite
|
Sign up to set email alerts
|

Sodium erythorbate, stable chlorine dioxide, and gellan gum glazing for shelf life extension of commercial peeled shrimp ( Litopenaeus vannamei ) during frozen storage

Abstract: The combined effect of sodium erythorbate, stable chlorine dioxide, and gellan gum glazing on quality of peeled shrimp was investigated during frozen storage, and compared with traditional water‐ice‐glazing treatment. Data revealed that the growth of total aerobes, Escherichia coli, and Staphylococcus aureus was significantly inhibited in the combined treatment, compared to the water‐ice‐glazing group. Examination of tissue texture and microstructure verified that the combined glazing effectively maintained sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…In fact, the textural parameters of shrimp could be affected by various factors. Among them, the stability of myofibrillar protein and the strength of connective tissue played the most important roles (Cao et al, 2019). In this study, these textural results firmly demonstrated the positive synergistic effect of hypotaurine-chitosan coating in textural properties for shrimp during storage.…”
Section: Analysis Of Textural Properties Changesupporting
confidence: 72%
“…In fact, the textural parameters of shrimp could be affected by various factors. Among them, the stability of myofibrillar protein and the strength of connective tissue played the most important roles (Cao et al, 2019). In this study, these textural results firmly demonstrated the positive synergistic effect of hypotaurine-chitosan coating in textural properties for shrimp during storage.…”
Section: Analysis Of Textural Properties Changesupporting
confidence: 72%
“…The gel strength after 120–180 days was not significantly different from that after 90 days ( p > 0.05), presumably because structural degradation had stopped by 90 days. Proteins in fish sausage oxidize and degrade during frozen storage as the hydratability of the proteins decreased, disrupting the gel network [ 36 ]. As a result, the fish sausages should be consumed within 4 months of purchase, as long-term storage will result in a significant decrease in gel strength and quality.…”
Section: Resultsmentioning
confidence: 99%
“…After the squid samples were frozen by an ultra-low temperature freezing chamber (Jiangsu Air Conditioner Co., Ltd., Jiangsu, China), to make the center of squid reached −18°C rapidly, these samples of frozen squids were transferred and stored at −30°C for 24 h. The frozen squid samples were subsequently immersed in the prepared distilled water (2°C) for 18 ~ 24 s, controlled the percentage of ice glazing (10% ± 1%). [21] Subsequently, the glazed samples were packed immediately in polyvinyl chloride bags and thereafter stored in the refrigerator for 6 months, at −5, −10, −20, −30, and −40°C, respectively. During this storage period, at specified intervals, all analyses were done for three randomly chosen samples for each storage temperature (three repetitions).…”
Section: Methodsmentioning
confidence: 99%